Direct‐acting antiviral agents for hepatitis C virus‐mixed cryoglobulinaemia: dissociated virological and haematological responses. (13th August 2020) - Pozzato, Gabriele; Mazzaro, Cesare; Artemova, Marina; Abdurakhmanov, Dzhamal; Grassi, Gabriele; Crosato, Ivo; Mauro, Endri; Ghersetti, Michela; Zorat, Francesca; Bomben, Riccardo; Bulian, Pietro; Gattei, Valter
Summary: The hepatitis C virus‐positive (HCV+) mixed cryoglobulinaemia (MC) is associated with haematological alterations such as monoclonal B‐cell lymphocytosis or non‐Hodgkin lymphomas (NHLs). Antiviral therapy for MC, based on interferon and ribavirin, has been shown to be able to eliminate the viral replication as well as the B‐cell monoclonal alterations. Many studies have reported the efficacy of direct‐acting antivirals (DAAs) in the treatment of HCV+ MC. However, some authors noticed the persistence of haematological diseases despite HCV eradication. To verify the effects of DAAs on B‐cell proliferation, we evaluated 67 patients with HCV+ MC. Six patients had an overt NHL and 30% had monoclonal B‐lymphocytosis. In 20% of the patients, the mutation L265P of the myeloid differentiation factor 88 ( MYD88 ) gene was detected in peripheral blood. All patients had negative HCV viraemia at week 12; one had a breakthrough, while two cases relapsed. A complete clinical response of vasculitis was seen in 60% of the patients. Among the six patients with NHL, one showed a complete response, whereas in the others there were no changes in the number and size of the nodes. Among the patients carrying a clonal population in peripheral blood, only 22% became negative. These data indicate that DAAs are not able to eliminate the clonal alterations induced by HCV in a large proportion of cases.